Programmed cell death ligand 1 (PD-L1, CD274) in cholangiocarcinoma: correlation with clinicopathological data and comparison of antibodies - Kriegsmann, Mark; Rössler, Stephanie; Kriegsmann, Katharina; Renner, Marcus; Longuespée, Rémi; Albrecht, Thomas; Löffler, Moritz; Singer, Stephan; Mehrabi, Arianeb; Vogel, Monika Nadja; Pathil-Warth, Anita; Köhler, Bruno Christian; et al. (BMC cancer, 2019)
Cholangiocarcinoma (CCA) may arise in the intra- or extrahepatic biliary tract and is associated with a poor prognosis. Despite recent advances, to date there is still no established targeted therapeutic approach available. Non-surgical therapeutic agents are urgently needed, as most patients are non-eligible to surgical resection. Anti-PD-L1 therapy prevents cancer cells from evading the immune system and has emerged as a new treatment option in several cancer entities. Recently, PD-L1 expression has been analyzed in comparably small CCA patient cohorts. However, a systematic validation of different PD-L1 antibodies has not been performed in CCA so far.
Gesehen am 10.05.2019